Molecular Imprinted Hydrogels in Drug Delivery Applications. Issue 1797 (14th May 2015) - Bates, Jeffrey S.; Whitson, Luke R.; Albertson, Kelan M.; Hickerson, Nathan S.; Nichols, Patrick E.; Larson, Bethany E.; Sparks, Taylor D.
ABSTRACT: Molecular imprinting is the process by which molecules are imprinted into the matrix of a material through non-covalent bonding, including hydrogen bonding and van der Waals interactions. In this study hydrogels were imprinted with glaucoma medication with the purpose of creating a reusable ocular drug delivery device with reversible binding sites. The material was synthesized and tested with UV-Vis spectroscopy to determine the concentration of the released drug after twelve hours in distilled water. Modifications were made to the polymer to explore methods required for the proper delivery of the drug over an adequate period of time.